ANALISIS PENGARUH RASIO LIKUIDITAS DAN RASIO AKTIVITAS TERHADAP PENILAIAN KINERJA KEUANGAN PADA PT. SELAPARANG FINANSIAL KABUPATEN LOMBOK TIMUR (2014-2018) - Muhamad Karyadi (Akuntansi research UGR, 2019)
The purpose of this study was to determine whether there is an influence between liquidity and activities on the company's financial performance. This research was conducted at PT. Selaparang Financial East Lombok Regency. Analysis of the data used in this research is by using multiple linear regression analysis and descriptive statistics and classical assumptions. Analysis of this data is done using SPSS 21 application software. Based on the results of the study it can be as follows: that the current ratio is not significant negative effect on ROE because the value of t is smaller than t table (-1.972 <2.5708) and the level of significance is less than 0.05 (0.187> 0.05). total assets turnover has no significant positive effect on ROE because the t value is smaller than t table (1,666 <2.5708) and the significance level is greater than 0.05 (0.238> 0.05). total assets turnover which is included in the activity ratio which will be able to influence the level of company performance by using ROE measurements. Based on the simultaneous test results obtained f count of 3,403. Because the calculated f value of 3,403 is smaller than the f value of table 5.05 with a Sig value of 0.227. Because the significance value of 0.227> 0.05 corresponds to the basis of decision making in the f test, it can be concluded that the Current Ratio (X1) and Total Assets Turnover (X2) simultaneously have no effect on Return on Equity (Y1).